الرسم العثماني وإعجازه في ضوء مذاهب العلماء: دراسة تحليلية - Mohamadou Bab Ahmuodi; Abdallah El Khatib; Mohammed Minhaj Uddin (Universiti Sains Islam Malaysia, 2026)
Maʿālim Al-Qurʾān Wa Al-Sunnah, Volume 21 Issue 2 Page (180–208)